Implementasi Metode Pembelajaran Mind Mapping pada Mata Pelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah Ruhul Islam Jakarta Selatan - Ika Kartika; Yanti Hasbian Setiawati; Saepudin Saepudin; Aman Aria Sunasa; Nova Dahliah Susanti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Madrasah Ibtidaiyah and Madrasah Trsanawiyah Ruhul Islam have accreditation status. The two Madrasahs were founded in 1973 and have teachers who perform quite well, but in general the learning activities carried out by teachers are still traditional, a small number of teachers master learning methods by utilizing digital technology. In learning the history of Islamic culture, teachers often encounter many obstacles, especially in the motivation and student learning outcomes. This Abdimas provides training on the application of the mind mapping method in general, an introduction to its benefits and how to apply it which can provide added value in the delivery of teaching materials because mind mapping is a new innovation in developing learning. In this training the teachers consisted of teachers for the Islamic Cultural History subject at the Ruhul Islam Madrasah Ibtidaiyah, and besides teachers for the Islamic Cultural History subject at the Ruhul Islam Madrasah Ibtidaiyah. The results obtained from this training had quite a positive impact, the partners expressed satisfaction with the training that had been carried out.